The Impact of Government Programs on Youth Startups in Uganda-Case Study of Emyooga Youth Startups in Mukono District - Edward Ayebare (Uganda Christian University, 2024)
This literature review focuses on the link between youth empowerment, skills development, and social entrepreneurship in Mukono Municipality and Lira City, especially at governmentprogram levels. The review synthesizes recent studies related to the effectiveness of various initiatives such as the YLP, Emyooga, and OWC in making the youth self-reliant through socio-economic development. This review shows that despite such positive contributions these programs have made to youth empowerment for self-reliance and the stimulation of entrepreneurship, there are still gaps that call for critical reflection. The key findings reveal advanced business management training and continuous learning towards the scaling up of ventures and adapting to changing market conditions. Other areas that have been highlighted include sensitization about programs, barriers to accessibility, and innovation in supporting youth entrepreneurship. These include the inclusion of advanced training modules, enhancement in the awareness of the program through comprehensive sensitization campaigns, increase in geographic and financial access, promotion of innovation, reinforcement in the levels of support by local authorities, and strong mechanisms for monitoring and evaluation. These recommendations shall have to be addressed if the programs on youth empowerment are to effectively achieve sustainable impacts on economic independence and community resilience in the region.
Undergraduate research